KEEFEKTIFAN PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN RASA INGIN TAHU ANAK USIA 3 - 4 TAHUN - Zumrotus Sa’adah; Arri Handayani; Anita Chandra D.S (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that prompted this research was the conditions found in the Al-Muttaqin family planning institution, Buko village, Wedung sub-district, Demak district, most of the children experienced problems in problem-solving skills. This was shown during the learning activities that researchers observed, children were still confused about various shapes, could not find solutions to simple problems such as children not knowing colors, and still looked very passive. Apart from that, based on researchers' observations, the learning activities carried out at this institution are still monotonous and limited. Educators still often use verbal methods and the minimal application of play media used in learning activities makes the learning process less attractive to students. The formulation of the problem in this research is "How is the effectiveness of project-based learning on the problem solving abilities of children aged 3-4 years" and "How is the effectiveness of project-based learning on the curiosity of children aged 3 -4 years". The objectives to be achieved in this research are to determine the effectiveness of project-based learning on the problem-solving abilities of children aged 3-4 years and to determine the effectiveness of project-based learning on the curiosity of children aged 3-4 years. This type of research is quantitative research. The population in this study were group A Muria children aged 3 - 4 years old PAUD KB Al Muttaqin Buko Wedung Demak who were in one class. Sampling in this study used a simple random sampling technique, namely that the sample was chosen randomly without paying attention to the strata contained in the population. For the data in this research, researchers used data collection techniques in the form of observation.